The Ordovician meteorite event in North America: age of the Slate Islands impact structure, northern Lake Superior, Ontario, Canada - Parisi, Andrew F.; Catlos, Elizabeth J.; Brookfield, Michael E.; Schmitt, Axel Karl; Stöckli, Daniel F.; Miggins, Daniel P.; Campos, Daniel S. (Meteoritics & planetary science, 2024)
The Slate Islands (Ontario) is one of Canada's larger impact structures at 32 km in diameter and has been linked to the Ordovician meteorite event (OME). We report zircon U-Pb dates from two suevite and two syenite samples collected from the Slate Islands. Plagioclase 40Ar/39Ar dates were also obtained from one of the samples. The plagioclase and most zircon dates record pre-impact ages with links to known tectonic events, including those associated with the assembly of the Superior Craton at approximately 2700 Ma. However, Neoarchean zircon grains appear to be reset at 456.1 ± 6.9 Ma (±2σ) based on the lower intercept of discordia for all dated samples. The date overlaps its previously accepted age of 450 Ma and would be 2-19 million years following the parent asteroid breakup if related to the OME.